Improving self-care behavior knowledge in hypertensive patients through jigsaw learning and educational booklets: A quasi-experimental study - Muhammad Anwar Haﬁd; Al-Fisyah, Dina (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2026)
Background: Hypertension remains a major global health problem with a high prevalence rate, necessitating effective educational strategies to improve patient self-care behaviors to prevent cardiovascular complications and premature death. Objectives: This study aims to analyze the effect of healthy lifestyle education using the Jigsaw method through a booklet medium on improving self-care behavior knowledge in hypertensive patients. Methods: A quasi-experimental design with a pretest-posttest control group approach was used, involving 58 hypertensive patients in the Benteng Community Health Center working area who were randomly allocated into the intervention and control groups. Data were collected using a hypertension self-care knowledge questionnaire consisting of 24 questions covering six important aspects and analyzed using the Cochran test to evaluate the effect of the intervention. Results: The results showed a significant difference between the intervention and control groups with a p-value of 0.000 (p < 0.05), indicating that the intervention group experienced a greater increase in self-care behavior knowledge. The intervention group showed a significantly higher increase in mean knowledge scores across all self-care domains compared to the control group, underscoring the superior effectiveness of the collaborative Jigsaw strategy in enhancing deeper understanding and knowledge retention. Conclusions: These findings indicate that the Jigsaw method is effective in improving patient understanding and empowerment in hypertension management. This study advocates the integration of a patient-centered peer-teaching approach into routine primary healthcare to optimize self-management and clinical outcomes in chronic disease care